2023
DOI: 10.1177/08863687231200802
|View full text |Cite
|
Sign up to set email alerts
|

Variable Pay Transparency in Organizations: When are Organizations More Likely to Open Up About Pay?

Alexandra Arnold,
Anna Sender,
Ingrid Fulmer
et al.

Abstract: Due to external pressures organizations are confronted with the need to increase pay transparency and communication. However, there is limited research that has looked at when organizations are more likely to open up about pay. This study explores whether organizations report different levels of pay transparency depending on the characteristics of their variable pay systems. Using data from HR professionals at 400 organizations collected in a multi-country study, we investigated how proportion of variable pay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Moreover, PayScale’s findings indicate that a substantial portion of responding firms which had yet to adopt such aggregated forms of pay outcome transparency were considering doing so even prior to the adoption of regulations (e.g., in California and New York City) requiring them to do so. Similarly, Arnold and colleagues (2018) report that 40 and 30% of the Swiss enterprises they surveyed disclosed, respectively, aggregate and exact individual-level base pay information to their employees; and 37 and 23%, respectively, disclosed aggregate and individual-level information on performance-based pay.…”
Section: Policy Implications For Organizational Leadersmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, PayScale’s findings indicate that a substantial portion of responding firms which had yet to adopt such aggregated forms of pay outcome transparency were considering doing so even prior to the adoption of regulations (e.g., in California and New York City) requiring them to do so. Similarly, Arnold and colleagues (2018) report that 40 and 30% of the Swiss enterprises they surveyed disclosed, respectively, aggregate and exact individual-level base pay information to their employees; and 37 and 23%, respectively, disclosed aggregate and individual-level information on performance-based pay.…”
Section: Policy Implications For Organizational Leadersmentioning
confidence: 95%
“…But even in the absence of such legislation, survey data suggest that organizations are becoming increasingly receptive to reducing restrictions on pay process information. For example, in their 2017 study of over 500 HR professionals in Switzerland, Arnold and her associates (2018) found that 69% of the firms in their study (public, private, and NGOs) informed employees about how benefits were determined; 50% provided similar information about base pay, pay raises, and team/organization-level variable pay; and 40% provided information on the determination of individual-level variable pay. Similarly, nearly two-thirds of the HR managers responding to a recent SHRM in the United States reported that they have clear guidelines for how base pay (63%) and raises (63%) are determined (Alterman et al, 2023).…”
Section: Policy Implications For Organizational Leadersmentioning
confidence: 99%